تأثير النشاط البدني الرياضي المكيف في تحسين بعض القدرات العقلية ( الإشارة - الإدراك الحركي) لدى فئة التخلف العقلي إعاقة ذهنية بسيطة - بالغالي, جمال (Institut d'Éducation Physique et Sportive - Mostaganem 2023/2024, 2024)
"ملخص البحث" عنوان الدراسة: أثر النشاط البدني الرياضي المكيف في تحسين الانتباه والادراك الحركي لدى فئة التخلف العقلي البسيط (09-13) سنة. -يهدف بحثنا هذا إلى معرفة تأثير برنامج النشاط البدني الرياضي المكيف في تطوير بعض الانتباه والادراك الحركي لدى فئة التخلف العقلي البسيط(09-13) سنة، حيث اعتمد الطالب على أسس علمية لتصميم واعداد البرنامج المناسب وخصائص العينة حيث طبق البرنامج المقترح على أطفال العينة التجريبية، وتمثلت فرضية الدراسة أن البرنامج المقترح للنشاط البدني الرياضي المكيف له تأثير ايجابي في تنمية الانتباه والادراك الحركي لدى فئة التخلف العقلي البسيط (09-13) سنة، وتم تحديد واختيار عينة البحث بطريقة مقصودة والبالغ عددهم 16 طفل منها 10 للعينة التجريبية و06 للضابطة، ولقد استخدمنا المنهـج التجـــــــــريبي، كما تمثلت أدوات البحث في اختبار بوردو لقياس القدرات الحركية الادراكية وكذلك مقياس الانتباه، وتمت معالجة البيانات بالاستعانة ببرنامج exel، فكانت أهم نتائج هذه الدراسة -التأثير الايجابي لبرنامج النشاط البدني الرياضي المكيف المقترح لأطفال العينة التجريبية حيث أنه ساهم في تنمية وتحسين القدرات الحركية الادراكية ورفع من مستوى الانتباه، في حين لم يحقق البرنامج التقليدي أو العادي تطورا كثيرا في نسبة هذه المهارات لدى اطفال المجموعة الضابطة، فنقول توجد فروق دالة إحصائيا في القياس البعدي بين المجموعتين التجريبية والضابطة في اختبارات القدرات الحركية الادراكية والانتباه قيد البحث وهذا لصالح المجموعة التجريبية، وفي الأخير خلصنا الى مجموعة من الاقتراحات والتوصيات أهمها استخدام برنامج النشاط البدني الرياضي المكيف لتأثيره الفعال في تطوير وتحسين القدرات الحركية الادراكية والانتباه لفئة التخلف العقلي البسيط (09-13) سنة. الكلمات المفتاحية: النشاط البدني الرياضي المكيف، الانتباه، الادراك الحركي، التخلف العقلي. // // // // // ResearchSummary Studytitle: The effect of adapted sports physicalactivity in improving attention and motorawarenessamongmild mental retardation category (09-13) years Our researchaims to know the effect of an adapted sports physicalactivity program in developingsome attention and motorawarenessamong the group of mild mental retardation (09-13) years.Thestudentrelied on scientificfoundations to design and prepare the appropriate program and the characteristics of the sample, as the proposed program wasapplied to the children of the experimentalsample. The hypothesis of the studywasthat the proposed program for adaptedphysicalsportsactivity has a positive effect in developing attention and motorawarenessamong the group of mild mental retardation (09-13) years. The researchsamplewasidentified and selected in an intentionalmanner, and itnumbered 16 children, including 10 for the experimentalsample and 06 for the control sample. Weused the experimentalmethod, and the researchtoolswere the Bordeaux test to measure cognitive motorabilities, as well as the attention scale, and the data wasprocessedusing the Excel program. The most important results of thisstudywere the positive effect of the adapted sports physicalactivity program proposed for the children of the experimentalsample, as itcontributed to the development and improvement of motorabilities. Cognition and raising the level of attention, while the traditional or regular program did not achievemuchdevelopment in the percentage of theseskillsamong the children of the control group, sowesaythatthere are statisticallysignificantdifferences in the post-measurementbetween the experimental and control groups in the tests of perceptualmotorabilities and attention under investigation, and thisis in favor of the experimental group. Finally, weconcludedwith a set of suggestions and recommendations, the most important of whichis ...the use of a physicalactivity program adapted to sports due to its effective impact on Developing and improving cognitive motorabilities and attention for mild mental retardation (09-13) years.
MAPA-2024-8
Keywords: النشاط البدني الرياضي المكيف - الانتباه، الادراك الحرك - التخلف العقلي